2014
DOI: 10.3855/jidc.3335
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance to cefotaxime and ertapenem in Enterobacteriaceae: the effects of altering clinical breakpoints

Abstract: Introduction: The Clinical and Laboratory Standards Institute (CLSI) updated its antimicrobial susceptibility testing interpretation criteria for Enterobacteriaceae. This study assessed the effects of clinical breakpoint changes in the CLSI 2009 to 2012 guidelines on antibiotic susceptibility testing reports. Methodology: In total, 2,076 non-duplicate clinical isolates of Enterobacteriaceae were analyzed. The disk diffusion method was used for susceptibility testing. The CLSI 2009-12 clinical breakpoints were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
1
8
0
2
Order By: Relevance
“…This was mainly attributed to increased CBPs for cephalosporins and fluoroquinolones. Liu et al observed a 10.5% increase in Enterobacteriaceae resistance rates to cefotaxime due to the CLSI CBP change from 2009 to 2010 guidelines, as well as 6.6% and 13.2% increase in resistance rates of K. pneumoniae, respectively [19]. However, the most likely causes of high MDR Gram-negative rates in this study are the overconsumption of antibiotics and the lack of both general and bacteria-specific healthcare strategies for prevention and control of hospitalacquired infections.…”
Section: Discussionmentioning
confidence: 99%
“…This was mainly attributed to increased CBPs for cephalosporins and fluoroquinolones. Liu et al observed a 10.5% increase in Enterobacteriaceae resistance rates to cefotaxime due to the CLSI CBP change from 2009 to 2010 guidelines, as well as 6.6% and 13.2% increase in resistance rates of K. pneumoniae, respectively [19]. However, the most likely causes of high MDR Gram-negative rates in this study are the overconsumption of antibiotics and the lack of both general and bacteria-specific healthcare strategies for prevention and control of hospitalacquired infections.…”
Section: Discussionmentioning
confidence: 99%
“…The change made by CLSI in the carbapenem breakpoints for Enterobacteriaceae (7) may have additionally reduced the rate of isolate susceptibility to these drugs, particularly for ertapenem (19) (20) . However, the major reason for the increase in K. pneumoniae resistance to carbapenems is probably the international dissemination of bacterial clones, such as the CC11 clonal complex, which express genes that regulate the carbapenemases, including Klebsiella pneumoniae carbapenemase (KPC), oxacillinase 48 (OXA-48), and New Delhi metallo-β-lactamase (NDM) (21) (22) .…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…With the implementation of the new breakpoints, it is anticipated that microbiology laboratories will be reporting more isolates as either intermediate or resistant to the tested antibiotics, potentially leading to increased prescribing of broad-spectrum antibiotics. An assessment of 2,076 nonduplicate clinical Enterobacteriaceae isolates using disk diffusion to compare the 2009 breakpoint to the 2010 breakpoint saw resistance to the thirdgeneration cephalosporin cefotaxime jump from 13.1% to 23.6% (16). Another assessment of 3,713 nonduplicate Gram-negative bacillus isolates with susceptibility determinations performed by disk diffusion using the CLSI 2009, CLSI 2010, CLSI 2011, and EUCAST 2011 guidelines found that, in aggregate, rates of resistance to cefepime, ceftriaxone, and ertapenem increased from (17).…”
Section: Clinical Impact Of Breakpoint Changes On Antimicrobial Stewamentioning
confidence: 99%